Proceeding with River Basin Management: legal, financial and political dimensions in Mongolia - Jean Carlo Rodríguez de Francisco; Annabelle Houdret; Ines Dombrowsky (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
As competition for water resources grows, a holistic management approach is required. Integrated Water Resources Management (IWRM) provides a coordinated, participative management framework to maximise economic and social welfare equitably, without compromising the sustainability of vital ecosystems. IWRM requires coordination at the national level for effective decision-making. Often IWRM is based on River Basin Management (RBM), which takes the river basin as the working unit for water management. Implementing RBM is not an easy task and levels of success differ between countries. This policy brief analyses the challenges that Mongolia faces as it continues down the IWRM/RBM path. Mongolia is an interesting case because of its rapid legal adoption of IWRM, its transition towards political decentralisation in its post-socialist era, and the tensions caused by a push for economic growth through mining activities. In particular, we analyse how to move from de jure to de facto RBM implementation. We structure our analysis and recommendations based on the political, legal, and financial dimensions that characterise water management decentralisation under the principles of IWRM. First, we find that regarding the legal dimension, Mongolia has made considerable progress in advancing the legal framework for IWRM/RBM and defining institutional responsibilities, both horizontally across sectors, as well as vertically across government levels. However, vertical coordination between the national and the river basin levels still needs improvement. The Ministry of Environment (MEGDT) and the National Water Committee (NWC) can further harmonise vertical coordination through different levels of government. Regulations for the implementation of water pollution fees need to be developed. Second, regarding the financial dimension, there is still ambiguity in some respects: In practice, River Basin Authorities (RBAs) remain underfunded and their financial resources are barely enough to cover their fixed costs. River Basin Councils (RBCs), as important as they appear to be in legal terms – allowing stakeholder participation in watershed management and decision-making – remain “paper tigers”, as they are not financially supported. Thus, stakeholder participation is marginal and in practice often only includes the participation of province (Aimag) and district (Soum) representatives, if any. Financing strategies related to the River Basin Management Plans (RBMPs) are needed. Third, on the political dimension, the development of the legal framework is an expression of the political will to implement RBM. This political will, however, remains half-hearted when it comes to enforcing environmental law, sparking participation, prioritising funding for respective water organisations and providing those organisations with the equipment required to fulfil their tasks. Aware of the current payment crisis, this paper argues for securing proper environmental conditions that sustain economic and social development in the long run.
Keywords: 330; Wasser